Pengaruh Investasi Infrastruktur Jalan Desa Terhadap Pendapatan Tambak Bandeng Di Desa Sobonon Kecamatan Totikum Kabupaten Banggai: The Effect of Village Road Infrastructure Investment on Milkfish Pond Income in Sobonon Village Totikum District Banggai Regency - Kismanto Muhsin; Taufik Bidullah; Suwardi Zakaria (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2019)
This study aims to determine the effect of rural road infrastructure investment on milkfish pond income in Sobonon village. The data used are primary data and secondary data using the interview method, observational literature study, operational definitions of variables consisting of independent and dependent variables, and variable measurement techniques, namely village road infrastructure investment (X), milkfish pond income (Y) and technical data analysis using simple linear regression, determinant coefficient test and statistical coefficient test t. The results of the correlation test for rural road infrastructure investment with the dependent variable, namely milkfish pond income, the R-value (correlation coefficient) is 0.886, the correlation value shows a very strong relationship because it is between 0.80 - 0.100. The determination test of village road infrastructure (X) on milkfish pond income (Y) in Sobonon village, Totikum subdistrict, Banggai Islands district is 78.6%, while 21.4% of rural road infrastructure investment is influenced by other variables not examined. The statistical coefficient test of the t-test t-count value is 3.914 > 3.182, so it can be concluded that Ho is rejected and Ha is accepted, which means that there is an effect of village road infrastructure investment (X) on milkfish pond income (Y).